An analysis of the "European City of Sports" project and its impact on the development of tourist activity: The example of selected Slovakian cities - Matušíková, Daniela; Švedová, Milena; Dzurov Vargová, Tünde; Żegleń, Patrycja (Turyzm/Tourism, 2020)
The paper presents the issue of sports activity development in the context of the European City of Sports project in selected Slovakian cities: Košice, Banská Bystrica and Nitra. It is an analytical overview aiming at the development of these cities for tourism through the organisation of international sporting events. Using several methods, especially comparison, the authors analyse certain activities and other sports-related issues. The events and activities not only contributed to the development of sport but also supported tourism in the region. A review of the literature on the subject demonstrates the importance and basic assumptions of the European City of Sports as a popular project. The comparative analysis has enabled the authors to present its results in each of the three Slovakian cities.